Legal Analysis of Digital Technology Integration in Legislation Design in Indonesia - Rahmat Dwi Putranto; Aisha Mutiara Savitri (Jurnal Pembaharuan Hukum, 2025)
The digital revolution in the era of Industry 4.0 has significantly transformed various aspects of social and governmental life, including the process of forming legislation. In Indonesia, this transformation is supported by the implementation of the Electronic-Based Government System (SPBE) and the enactment of Law Number 13 of 2022 as an amendment to Law Number 12 of 2011 on the Formation of Legislation. This study aims to analyze the legal regulation of digital technology integration in the legislative process, examine the implementation of the digital legislation system in Indonesia, and identify the legal and institutional challenges arising from this integration. The research employs a normative legal research method with a descriptive qualitative approach by analyzing primary legal materials, including relevant laws and regulations, as well as secondary legal materials such as legal literature and scholarly works. The results show that Law Number 13 of 2022 provides a strong legal basis for the digitalization of legislative processes and enhances transparency and public participation. However, challenges remain in terms of infrastructure disparities, limited human resources, and system interoperability. Therefore, continuous legal reform and institutional readiness are essential to ensure effective and accountable digital legislation.